Spondias purpurea L. (Anacardiaceae): Antioxidant and Antiulcer Activities of the Leaf Hexane Extract. (26th October 2017) - de Almeida, Cynthia Layse Ferreira; Brito, Samara Alves; de Santana, Temístocles Italo; Costa, Henrique Bandeira Alves; de Carvalho Júnior, Carlson Helder Reis; da Silva, Márcia Vanusa; de Almeida, Lécio Leone; Rolim, Larissa Araújo; dos Santos, Vanda Lucia; Wanderley, Almir Gonçalves; da Silva, Teresinha Gonçalves
Abstract : Spondias purpurea is used in folk medicine to treat diarrhea and diuresis. The objective of this study was to evaluate the phytochemical profile and antioxidant and antiulcer activities of the hexane extract of the leaves of S. purpurea (SpHE). Phytochemical profile was evaluated via thin layer chromatography (TLC) and HPLC. SpHE was screened for antioxidant activities using DPPH, ABTS, FRAP, and phosphomolybdenum assays. To determine its antiulcer properties, animals were pretreated with injured control, lansoprazole, ranitidine, carbenoxolone, or SpHE (12.5, 25, and 50 mg/kg) and were screened; acute ulcers were induced by HCl/ethanol, absolute ethanol, and nonsteroidal anti-inflammatory drug (NSAID). TLC revealed the presence of flavonoids, whereas HPLC analysis showed the presence of caffeic acid and epigallocatechin. The phenolic compounds and in vitro assays showed antioxidant activity. After gastric ulcer induction by using HCl/ethanol, SpHE reduced the area of ulcerative lesions by 82, 91, and 88%, respectively. In ethanol, SpHE reduced the area of ulcerative lesions by 77, 93, and 92%, respectively. In the NSAID, the percentages of protection were 70, 76, and 78%, respectively. SpHE promoted the minimization of ulcers, increased the levels of reduced glutathione, and decreased tumor necrosis factor. S. purpurea has antioxidant and antiulcer properties.